Enhancing students’ mathematical thinking through culturally responsive algebra instruction using interactive Google Slides - Dosinaeng, Wilfridus Beda Nuba; Leton , Samuel Igo; Djong, Kristoforus Djawa; Uskono, Irmina Veronika; Jagom, Yohanes Ovaritus; Lakapu, Meryani (Universitas Papua, 2025)
Algebra plays a vital role in developing students' higher-order thinking skills; however, in many junior high schools, algebra instruction remains focused on mechanical procedures rather than conceptual understanding and contextual problem solving. This approach limits students' ability to engage meaningfully with mathematical content, particularly in culturally diverse classrooms where learning materials often lack relevance to students’ lived experiences. To address this gap, this study presents the development of culturally grounded algebra learning materials using Google Slides, chosen for its accessibility, interactivity, and collaborative features, which offer distinct advantages over conventional static media. The study employed the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model within a Research and Development (R&D) framework to systematically design and evaluate the learning materials. Conducted with seventh-grade students at SMP Lorotuan using a pretest-posttest design, the results revealed a significant increase in student achievement, with scores improving from 45.36 to 86.61 and an N-Gain value of 0.42, classified as moderate by Hake’s standard. Observations and survey data confirmed the materials’ practicality and strong cultural relevance, with students awarding a perfect cultural relevance score (560/560) and reporting increased appreciation for their local culture. This study concludes that integrating local wisdom into interactive algebra instruction can effectively enhance students’ mathematical understanding and cultural identity. The findings support the continued development of culturally responsive digital learning tools that address diverse student needs and promote equitable mathematics education.